2012
DOI: 10.1089/jmf.2010.0299
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and Cardioprotective Effects of Pumpkin Seed Oil

Abstract: Pumpkin seed oil is a natural product commonly used in folk medicine for treatment of prostatic hypertrophy. In the present study, the effects of treatment with pumpkin seed oil on hypertension induced by the nitric oxide synthase inhibitor N(ω)-nitro-L-arginine methyl ester hydrochloride (L-NAME) (50 mg /kg/day) in rats were studied and compared with those of the calcium channel blocker amlodipine. Pumpkin seed oil (40 or 100 mg/kg), amlodipine (0.9 mg/kg), or vehicle (control) was given once daily orally for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…In the present study l -NAME induced a time-dependent significant elevation of systolic blood pressure, significant decrease of pulse rate, significant decrease in serum nitric oxide metabolites and significant increase in collagen I and III genes expression in the hearts along with the highest histopathological grade (3) for interstitial fibrosis among all studied groups. The data of the present study are in accordance with the findings of Gonzalez et al [13] who found in addition decrease in cGMP content of the arterial wall, and with El-kharashi et al [14] and El-Mosallamy et al [12] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study l -NAME induced a time-dependent significant elevation of systolic blood pressure, significant decrease of pulse rate, significant decrease in serum nitric oxide metabolites and significant increase in collagen I and III genes expression in the hearts along with the highest histopathological grade (3) for interstitial fibrosis among all studied groups. The data of the present study are in accordance with the findings of Gonzalez et al [13] who found in addition decrease in cGMP content of the arterial wall, and with El-kharashi et al [14] and El-Mosallamy et al [12] .…”
Section: Discussionsupporting
confidence: 93%
“…After that animals were sacrificed for heart dissection to detect collagen type I and III gene expression and for histopathological study. Nitric oxide was determined in serum according to the method of El-Mosallamy et al [12] .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, hemp seeds have a high level of antihypertensive activity because l -arginine, the precursor of NO, exists in abundance (Girgih et al, 2014 ). Pumpkin seeds are also known to lower BP because of their abundant l -arginine, which inhibits the production of MDA in a hypertension model induced by N(ω)-nitro- l -arginine methyl ester hydrochloride and facilitates NO production (El-Mosallamy et al, 2012 ). In addition, the finding that NO production was most active in the 3-mixed juice treatment group was consistent with the vitamin C and E contents.…”
Section: Resultsmentioning
confidence: 99%
“…• Cucurbita, squash, pumpkin, zucchini, some gourds idant, pumpkin seeds were shown to have protective activity against cardiovascular diseases and non-alcoholic fatty liver disease, by improving plasma lipid profile, lowering blood pressure and attenuating arthrosclerosis development (24)(25)(26). Bioactive macromolecules, such as Tocopherol, Trigonelline, Nicotinic acid and D-chiro-inositol, found in pumpkin seeds, possess hypoglycemic properties and could assist in maintaining glycemic control (27,28).…”
Section: Botanical Aspectsmentioning
confidence: 99%